Literasi Digital dan Integrasi Teknologi TPACK pada Buku Teks Bahasa Indonesia Kelas XI - Anggun Fatma Mustika; Maulinda Nurul; Umi Nur Sholikhah; Elen Inderasari (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
ABSTRACT This study aims to examine the form of digital literacy and technology integration in Indonesian language textbooks grade XI in the Merdeka Curriculum. The study using a qualitative descriptive approach, using the book "Cerdas Cergas Berbahasa dan Bersastra Indonesia" as the main object. Data were obtained through document analysis with the content analysis method, based on digital literacy theory and the TPACK technology integration model. The results of the analysis show that elements of digital literacy and technology integration have begun to be implemented in textbooks, but their application has not been fully integrated into the learning process. The forms of digital literacy identified include the inclusion of links (3), the use of QR Codes (14), and the use of educational applications (4). The presence of these features contributes to the development of digital literacy skills, information navigation skills, and technology-based interactive learning. However, this technology integration is still additional and has not become a core part of all learning activities. Based on these findings, the study recommends the need to strengthen and expand the integration of technology in textbooks so that they can maximally support the development of students digital literacy according to the needs of 21st century learning. Keywords: Indonesian Language Textbooks; Digital Literacy; Grade XI Senior High Schools